Primary Plasmacytoma Involving Kidney, Ureter & Urinary Bladder - ATM Mowladad Chowdhury,; Md Sazzad Hossain,; Md Mostakim Maoya, (Bangladesh Journal of Urology, 2025)
Primary plasmacytoma of urinary tract is extremely rare clinical entity, presenting diagnostic challenges due to its paucity of evidence. We are presenting a case of primary plasmacytoma of kidney, ureter & urinary bladder in a 74-year-old female patient. Computed tomography (CT) revealed that the mass was in the pelvis of the right kidney invading the renal vein, ureter & urinary bladder along with enlarged right paracaval lymph nodes. After optimization, radical right nephroureterectomy done with excision of cuff of bladder mucosa and the retroperitoneal lymph nodes was resected. Histopathological examination revealed plasmacytoma involving renal parenchyma, ureter & bladder with lymph nodes, which was confirmed by immunohistochemistry studies. Following this unexpected diagnosis, various examinations were performed, but there was no evidence of systemic plasma cell disease. Although the general prognosis and outcome of extra medullary plasmacytoma (EMP) is good, regular follow-up is recommended due to the possibility of relapse or progression to plasma cell neoplasm (PCN). This case is presented for reference, as it is imperative to keep plasmacytic tumours in mind and to include them in the differential diagnosis of anaplastic tumours, even in unusual location, such as the urinary system. Bangladesh J. Urol. 2025; 28(1): 49-51